Analisis praanggapan dalam Iklan Produk Kecantikan di Youtube - Erma Zevira; Armia Armia; Subhayni Subhayni; Ramli Ramli (JIM Pendididikan Bahasa dan Sastra Indonesia, 2019)
Based on the background of the problem, the problem formulation in this study is what is the presupposition in the advertisement of beauty products on Youtube? and what are the types of presuppositions in beauty product advertisements on Youtube. This study aims to describe presuppositions in beauty product advertisements on Youtube and to describe the types of presuppositions in beauty product advertisements on Youtube?. In this study, the authors choose 15 data sources for advertising beauty products "Ponds Instabright Tone Up cream", “Pantene” shampoo, “Garnier Sakura White "booster serum, Fair and Lovely, lotion "Citra Sakura Fair UV ", lotion "Nivea Instant White" serum, deodorant "Nivea Whitening Silk Touch", "Wardah Perfect Bright" creamy foam, "Wardah Lightening Two Way Cake" powder, "Maybelline Fit Me" powder, "Wardah Lightening Whip" facial foam, lotion "Vaseline" body yogurt ", lipstick “Pixy” lip cream, “Perfect Bright” micellar water, “Perfect Bright” micellar water, and “Ellips” hair vitamin. The results of this study indicate that there are six presuppositions in beauty product advertisements, namely (1) there are 26 existential presuppositions that are found in the form of presuppositions marked by nouns, nominal phrases, place descriptions, and time statements, (2) 20 factive presuppositions that are found by verbs, verbal phrases, adjectives, adjective phrases, and numeral phrases, (3) 7 lexical presuppositions found several presuppositions marked by special lexical expressions that give rise to presuppositions with other statements that are conceptually not directly stated in the speech, (4) 2 non-active presuppositions found in the form of presuppositions marked by verbs and conjunctions, (5) 2 structural presuppositions found in the form of presuppositions marked by 0question 0words, (6) 1 counterfactual presuppositions0found 0in 0the 0form of contradictory sentences from the speech